The Neurotoxin DSP-4 Induces Hyperalgesia in Rats that is Accompanied by Spinal Oxidative Stress and Cytokine Production. (15th April 2018) - Touchette, Jillienne C.; Little, Joshua W.; Wilken, Gerald H.; Salvemini, Daniela; Macarthur, Heather
Highlights: DSP-4 reduces norepinephrine levels in rat spinal cord. DSP-4 induces oxidative stress and increased inflammatory cytokine levels in the spinal cord. DSP-4 treated rats develop thermal and mechanical hypersensitivity. Abstract: Central neuropathic pain (CNP) a significant problem for many people, is not well-understood and difficult to manage. Dysfunction of the central noradrenergic system originating in the locus coeruleus (LC) may be a causative factor in the development of CNP. The LC is the major noradrenergic nucleus of the brain and plays a significant role in central modulation of nociceptive neurotransmission. Here, we examined CNS pathophysiological changes induced by intraperitoneal administration of the neurotoxin DSP-4 (N-(2-chloroethyl)-N-ethyl-2-bromobenzylamine hydrochloride). Administration of DSP-4 decreased levels of norepinephrine in spinal tissue and cerebrospinal fluid (CSF) and led to the development of thermal and mechanical hyperalgesia over 21 days, that was reversible with morphine. Hyperalgesia was accompanied by significant increases in noradrenochrome (oxidized norepinephrine) and expression of 4-hydroxynonenal in CSF and spinal cord tissue respectively at day 21, indicative of oxidative stress. In addition, spinal levels of pro-inflammatory cytokines (interleukins 6 and 17A, tumor necrosis factor-α), as well as the anti-inflammatory cytokine interleukin10 were also significantly elevated at day 21, indicating that an inflammatory response occurred. The inflammatory effect of DSP-4 presented in this study that includes oxidative stress may be particularly useful in elucidating mechanisms of CNP in inflammatory disease states.